15R SrMn1-xFexO3-δ (x ≈ 0.1); A New Perovskite Stacking Sequence - Cussen, E; Sloan, J; Vente, J; Battle, P; Gibb, T (1998)
A polycrystalline sample of a new phase in the Sr-Fe-Mn-O system has been prepared by standard solid-state techniques. Characterization at room temperature by X-ray diffraction, high-resolution electron microscopy, Mössbauer spectroscopy and neutron diffraction has led to it being described as a 15-layered, rhombohedral (15R) perovskite [space group R3̄m: a = 5.4489(1) Å, c = 33,8036(7) Å] with a previously unobserved structure. The pseudo close-packed SrO3 layers have a (cchch)3, stacking sequence such that the occupation of the interstitial 6-coordinate sites by Mn (or Fe) leads to the formation of Mn2O9 units which are linked to each other either directly by a common vertex, or indirectly via a single, vertex-sharing MnO6 octahedron. The stoichiometry of the compound was determined to be SrMn0.915(5)Fe0.085(5)O2.979(3). The face-sharing sites are occupied by 0.957(3)Mn/0.043(3)Fe while the exclusively corner-linked sites show a higher Fe occupation; 0.745(4)Mn/0.255(4)Fe. A neutron diffraction experiment carried out at 3 K indicated the presence of long-range magnetic order with the Mn4+ cations aligned antiferromagnetically with an ordered moment of 2.26(3)/μB/Mn4+. Both the neutron and the susceptibility data are consistent with the Fe cations remaining magnetically disordered to 3 K. The latter data show TN = 220 K, and suggest that some spin frustration is present at low temperatures.